Three metal complexes derived from 3-methyl-1H-pyrazole-4-carboxylic acid: synthesis, crystal structures, luminescence and electrocatalytic properties. Issue 57 (27th May 2016) - Liu, Jing; Cheng, Mei-Ling; Yu, Li-Li; Chen, Sheng-Chun; Shao, Yong-Liang; Liu, Qi; Zhai, Chang-Wei; Yin, Feng-Xiang
Abstract : [Cd(HMPCA)2 (H2 O)4 ] (1 ), [Co(H2 MPCA)2 (DMF)2 (H2 O)2 ]Cl2 (2 ), and [Cd3 Cl2 (HMPCA)4 (H2 O)2 ]·2H2 O (3 ) have been synthesized. As a bifunctional catalyst, complex2 exhibited excellent catalytic activity for OER and certain catalytic activity for ORR. Abstract : Mononuclear complexes [Cd(HMPCA)2 (H2 O)4 ] (1 ) and [Co(H2 MPCA)2 (DMF)2 (H2 O)2 ]Cl2 (2 ), and 3D coordination polymer [Cd3 Cl2 (HMPCA)4 (H2 O)2 ]·2H2 O (3 ) (H2 MPCA = 3-methyl-1 H -pyrazole-4-carboxylic acid) were synthesized and characterized by elemental analysis, IR spectra, thermogravimetric analysis, and X-ray single-crystal structure analysis. In3, HMPCA − anions bridged trinuclear Cd(ii ) ions clusters to form an 8-connected 3D network with channels. The complexes all display green fluorescence in the solid state. As a bifunctional catalyst, complex2 exhibited excellent catalytic activity for oxygen evolution reaction (OER), and certain catalytic activity for oxygen reduction reaction (ORR).